2023
DOI: 10.1007/s10644-023-09521-9
|View full text |Cite
|
Sign up to set email alerts
|

Does green credit policy promote corporate green innovation? Evidence from China

Abstract: Green innovation is an important strategy for companies to achieve sustainable development goals. In addition to helping companies create a green image and improve their competitive advantage, green innovation can reduce pollution and improve the ecological and social environment, with positive external effects. The green credit policy (GCP) is an addition to traditional environmental regulations. Taking the 2012 Green Credit Guidelines as a quasi-natural experiment, this study finds that GCP significantly red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 88 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…The findings of this study add to the growing body of literature emphasizing the role of regulatory policies in promoting green innovations. For instance, studies by Yin et al (2023) [9] and Liu et al (2023) [10] have similarly found that government policies can drive corporate behavior towards more sustainable practices. However, our research extends these findings by highlighting the differential impact of the water resource fee-to-tax policy on different types of green innovations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study add to the growing body of literature emphasizing the role of regulatory policies in promoting green innovations. For instance, studies by Yin et al (2023) [9] and Liu et al (2023) [10] have similarly found that government policies can drive corporate behavior towards more sustainable practices. However, our research extends these findings by highlighting the differential impact of the water resource fee-to-tax policy on different types of green innovations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the critical factors driving corporate green energy-saving innovation have also been actively explored by scholars in the past, including digital transformation [3], green financial instruments [4], green subsidies [5], corporate size [6], financing constraints [7], and executives' environmental awareness [8], with most scholars focusing on the impact of policy and regulatory systems on green energy-saving innovation based on China's current situation and political system [9,10]. As the "visible hand" in economic development, government policies profoundly impact corporate operations and strategic decision making [11].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the specialized products and services of green finance can provide enterprises with financial resources and alleviate their financial difficulties (Yin, Wang, Lu, & Liu, 2023), which motivates them to innovate. Secondly, green finance also plays a supervision role, i.e., "Green Credit Guidelines", which can help curb managers' inefficient investments.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%